Impact of nurse champion on quality of care and outcomes in type 2 diabetes patients. Issue 1 (March 2019) - Wilson, Madison; Chen, Huey-Shys; Wood, Marilynne
Abstract : ABSTRACT: Over 29 million people in the United States have diabetes, with an additional 86 million living with prediabetes. On inpatient hospital units it is estimated that 50% of admitted patients have diabetes as a primary or secondary diagnosis. Nurse champions have improved outcomes and quality of life for patients across different clinical settings. The purposes of this evidence literature review are to evaluate and synthesize evidence regarding the impact of a nurse champion model on nurses' performances and diabetic patient health outcomes. Nurse champions in this review also refer to clinical nurse specialists, certified diabetes educators, and clinical mentors. Search of evidence-based literature was conducted using PubMed, CINAHL, Ovid, Cochrane Library, and Google Scholar databases. Keywords included Nurse Champion and Diabetes, Clinical Mentor and Diabetes, and Diabetes Educator. Search limits included date of publication within last 15 years, English language, and peer-reviewed journals. A total of 14 articles were included in the synthesis of literature with level of evidence ranging from I to V. The study designs of selected evidence fluctuate from randomized controlled trials (3), case studies (6), qualitative studies (2), systematic review (1), and quasi-experimental study (1). The synthesis of evidence indicated that implementation of a nurse champion model did not only significantly improve nurses' diabetic knowledge and skills, but also improved the health outcomes of diabetic patients including reduction in hemoglobin A1c levels, reduction in perceived Diabetes Distress Scale, quality of life improvement, reduction of number of near misses, decreased readmission rates, improved hypoglycemic outcomes, and greater weight loss in patients with type 2 diabetes. Improving diabetic patient outcomes could save the hospital a significant amount of money and create a higher standard of care across the healthcare field. Bettering patient outcomes are good not only for the patient but also the hospital and nurses. Implementation of nurse champion models into nursing practice could significantly improve patient outcomes and quality of life as well as nursing performance. Nurse champion models also can create new leadership roles in nursing.